Հայոց ցեղասպանության մեջ կայսերական Գերմանիայի մեղսակցության հարցի արտացոլումը խորհրդահայ պատմագրությունում - Արամ Միրզոյան (ՀՀ ԳԱՍ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
В статье рассмотрен вопрос ответсвенности Германии в геноциде армян а Османской империи, отраженный в армянской историографии советского периода. Во всех трудах, в основном, признана соучастие кайзеровской Германии в трагедии армянского народа. В частности, это отрицательная оценка политике правительства кайзеровской Германии и её представителям в Турции.In the article is examined the issue of complicity of Germany in the Armenian genocide in Ottoman Empire, mirrored in the Armenian historiography of the Soviet time. The complicity of Imperial Germany in the tragedy of the Armenian nation has been basically recognized in all works. In particular, there is the negative assessment of the policy of government of Imperial Germany and its representatives in Turkey.
Keywords: Պատմագրություն; Հայոց ցեղասպանություն (1915)